Use of the Advanced Lung Cancer Inflammation Index as a Prognostic Indicator for Patients With Cholangiocarcinoma - Wu, Huasheng; Ding, Fadian; Lin, Meitai; Shi, Zheng; Mei, Zhengzhou; Chen, Shaoqin; Jiang, Chao; Qiu, Huabin; Zheng, Zhenhua; Chen, Youting; Zhao, Peng (Frontiers in Surgery, 2022)
Background This study aimed to assess the clinical utility of the advanced lung cancer inflammation index (ALI) as a prognostic indicator for patients with cholangiocarcinoma (CCA) and construct a prognostic nomogram based on ALI. Methods A total of 97 CCA patients who received radical resection were included. The optimal cut-off point for ALI was identified by X-tile analysis. COX regression analyses were used to identify risk factors of overall survival (OS) and disease-free survival (DFS). A predictive nomogram for DFS was constructed. Results The optimal preoperative ALI cut-off value was 31.8. 35 (36.1%) patients were categorized into the low-ALI group and 62 (63.9%) patients into the high-ALI group. Low ALI was independently associated with hypoproteinemia and lower BMI (all P < 0.05). COX regression analysis revealed that preoperative ALI level (HR = 0.974, P = 0.037) and pathological TNM stage (HR = 7.331, P < 0.001) were independently correlated with OS for patients with CCA, and preoperative ALI level (HR = 0.978, P = 0.042) and pathological T stage (HR = 1.473, P = 0.035) remained to independent prognostic factors for DFS in CCA patients. Time-dependent ROC analysis, we found that ALI was better at predicting prognosis than other parameters, such as neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), and prognostic nutritional index (PNI) in terms of OS and DFS. A nomogram predicting DFS was built (C-index: 0.73 95%CI: 0.67-0.79). Conclusions ALI may be useful for prognosis assessment for patients with CCA.